PENGELOLAAN POTENSI BADAN USAHA MILIK DESA (BUMDES) DALAM MENINGKATKAN PENDAPATAN ASLI DESA DI KECAMATAN BONEPANTAI KABUPATEN BONE BOLANGO - Citra Amanda Harun; Fenti Prihatini Dance Tui; Romy Tantu (Kybernology Jurnal Ilmu Pemerintahan dan Administrasi Publik, 2024)
This research aims to determine and analyze (1) the management of the potential of Village-Owned Enterprises (BUMDes) in increasing village original income in Bonepantai District, Bone Bolango Regency. (2) factors that determine the success of managing the potential of Village-Owned Enterprises (BUMDes) in increasing original village income in Bonepantai District, Bone Bolango Regency. This research uses a qualitative descriptive approach with data collection techniques in the form of interviews, observation and documentation. The main informants consisted of sub-district heads, BPD chairs, BUMDes managers, BUMDes supervisors, MSME actors and local communities. Secondary data was obtained from official documents such as BUMDes operational reports and village administration documents. The research results show that the management of BUMDes potential in Bonepantai District has been carried out through more structured planning, organization that focuses on efficiency, implementation of sustainability-oriented business activities, as well as strict supervision and evaluation. This effort has contributed to improving the village's PADes and the economy of village communities. Factors that determine the success of BUMDes management include optimizing natural resources, budget and village human resources. Active support from local government, a strong social model, and high community participation are the main drivers of BUMDes' success in improving community welfare and the local economy. By strengthening the management system and increasing community participation, BUMDes in Bonepantai District has the potential to become an inspiring model for village-based local economic empowerment.